GENDER INFLUENCE ON UNDERGRADUATES’ INFORMATION LITERACY SKILLS IN THE USE OF INTERNET RESOURCES FOR LEARNING IN KWARA STATE, NIGERIA - Kofo, Soetan Aderonke; Mercy, Ominuta Itohan (MOJES: Malaysian Online Journal of Educational Sciences, 2018)
Information literacy skills are the ability that enables learners to successfully surf the internet in search of information to improve learning. The internet is a platform that consists of different resources where learners can search for and retrieve information. However, undergraduates do not possess the skills to surf the internet, find and use needed information and filter out irrelevant ones. This study was a descriptive research of the survey type. The objectives were to: (1) Examine the information literary skills possessed by undergraduate students. (2) Determine gender influence on the information literacy skills of undergraduates in the use of internet resources in Kwara State, Nigeria. 294 undergraduates were purposefully selected based on school proprietorship (Federal, State and Private). Israel model (2013) was used to determine the sample size. Two research questions were raised and answered using mean, frequency counts and percentage while one hypothesis was generated and tested using t-test statistic. The findings of the study showed that: i. Undergraduates possessed task definition with grand mean of (3.54) located and assessed information with grand mean of (3.43) and synthesis skills with grand mean of (3.37). ii. there was a significant difference between male and female students’ information literacy skills on the use of internet resources for learning t(292)=2.86,p<.05 in favour of the male. Female undergraduates should be encouraged to develop interest in surfing the internet for relevant learning resources.